2010
DOI: 10.1021/ie9015478
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of PH3 Decomposition Reaction over Amorphous CoNiBP Alloy Supported on Carbon Nanotubes

Abstract: The carbon nanotubes (CNTs) supported amorphous CoNiBP catalyst is synthesized by means of induced electroless-plating method. The morphology, structure, and composition of the catalyst are characterized using a number of analytical instrumentations including transmission electron microscopy, X-ray diffraction, BET surface area measurement, and inductively coupled plasma. The activity of the catalyst in phosphine decomposition reaction is measured and correlated with its surface and structural properties. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Table shows that the molar ratios of P/M in the Fe 2 O 3 /CNTs-S, Co 3 O 4 /CNTs-S, Co/CNTs-S, NiO/CNTs-S, and Ni/CNTs-S are 1.2, 1.3, 1.2, 2.3, and 2.5 respectively, approximating to the stoichiometry of FeP, CoP, and NiP 2 . The result is consistent with our previous studies on cobalt metal and cobalt alloy prepared by impregnation and induced electroplating technique. , …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Table shows that the molar ratios of P/M in the Fe 2 O 3 /CNTs-S, Co 3 O 4 /CNTs-S, Co/CNTs-S, NiO/CNTs-S, and Ni/CNTs-S are 1.2, 1.3, 1.2, 2.3, and 2.5 respectively, approximating to the stoichiometry of FeP, CoP, and NiP 2 . The result is consistent with our previous studies on cobalt metal and cobalt alloy prepared by impregnation and induced electroplating technique. , …”
Section: Resultssupporting
confidence: 93%
“…In order to create more defects and holes, increase BET surface area, and develop hydrophilic surface groups on the walls of the CNTs, the CNTs were pretreated before the active components were impregnated. The details about the pretreatment procedure are described in our previous publication . The CNTs used in this study are aligned multiwall carbon nanotubes which were purchased from Shenzhen Nanotech Co., Ltd., China.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, nanoscale amorphous alloys have been widely used in the field of catalysis and hydrogen storage due to their excellent physical and chemical properties, such as short-range order, long-range disorder, and good dispersion. In particular, metal-doped Ni–B amorphous alloys have attracted much attention owing to their excellent catalytic performance, low cost, and environmentally benign nature. For instance, Li et al have reported that Co-doped Ni–B amorphous alloys exhibited higher activity and chemoselectivity than the undoped system in the liquid phase hydrogenation of acetonitrile, and the effect of the quantity of Co was investigated in detail . Although addition of metals to amorphous alloys can increase dispersion and therefore their activities, agglomeration phenomena still exist sometimes leading to decreased activity, so it continues to be of great importance to find other effective modifiers. , Accordingly, polymers have been employed to prevent agglomeration of active components in catalysts, resulting in better dispersion and higher activity in catalytic hydrogenation. For instance, Liaw et al have reported that the particle sizes of a Co–Ni–B catalyst can be effectively controlled by using polyvinylpyrrolidone (PVP) as a modifier and the polymer-modified catalyst was more active than the unmodified one in the hydrogenation of unsaturated aldehydes .…”
Section: Introductionmentioning
confidence: 99%